Human Resources Skills and Agricultural Product Selling Power Through A Workshop on Processing Tomatoes Into “Torakur” Sweets - Niswah, Nihlatun; Wibowo, Laksono Yogi; Hanannika, Laudhira Kinantya; Adillah, Luthfiana Nur; Muayanah, Muayanah; Fatoni, Muhamad; Mukaromah, Neni; Sintawati, Mukti; Dewi, Kirana Prama; Supriyanto, Agus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
The high volume of tomatoes during the peak harvest season often results in low selling prices and financial losses for farmers. This problem is exacerbated by the limited shelf life of tomatoes and the lack of skills in processing the harvest into high-value products. To address this problem, a leadership project was implemented to improve the skills of family welfare empowerment (FWE) mothers in the Dirgantara Asri Housing Complex in utilising tomato harvests to make products with high market value. The purpose of this workshop was to improve the skills of the community, especially among FWE mothers in the Dirgantara Asri Housing Complex, through training in processing tomatoes into a candied product called “Torakur” (Tomatoes with Date Flavour), which has significant market potential. Furthermore, participants are expected to market this processed product directly and through social media promotion efforts. The implementation method includes delivering educational materials, demonstrations of processing tomatoes into “Torakur,” and simple packaging and marketing techniques, both directly and digitally. This workshop aims to improve the skills of FWE mothers in producing and marketing “Torakur” independently, thereby creating sustainable local business opportunities. The measurement results were 100% very satisfied and 87.25% very useful. The results of this community service initiative show that the workshop has positively impacted community empowerment and strengthened interdisciplinary collaboration. Abstrak Tingginya volume tomat selama musim panen raya seringkali mengakibatkan harga jual yang rendah dan kerugian finansial bagi petani. Masalah ini diperparah oleh terbatasnya masa simpan tomat dan kurangnya keterampilan dalam mengolah hasil panen menjadi produk bernilai tinggi. Untuk mengatasi masalah ini, sebuah proyek kepemimpinan dilaksanakan untuk meningkatkan keterampilan ibu-ibu pemberdayaan kesejahteraan keluarga (PKK) di Perumahan Dirgantara Asri dalam memanfaatkan hasil panen tomat untuk menghasilkan produk bernilai pasar tinggi. Tujuan lokakarya ini adalah untuk meningkatkan keterampilan masyarakat, khususnya ibu-ibu PKK di Perumahan Dirgantara Asri, melalui pelatihan pengolahan tomat menjadi manisan “Torakur” (Tomat Rasa Kurma), yang memiliki potensi pasar yang signifikan. Selanjutnya, para peserta diharapkan dapat memasarkan produk olahan ini secara langsung dan melalui promosi di media sosial. Metode pelaksanaannya meliputi penyampaian materi edukasi, demonstrasi pengolahan tomat menjadi “Torakur”, serta teknik pengemasan dan pemasaran sederhana, baik secara langsung maupun digital. Lokakarya ini bertujuan untuk meningkatkan keterampilan ibu-ibu PKK dalam memproduksi dan memasarkan “Torakur” secara mandiri, sehingga menciptakan peluang usaha lokal yang berkelanjutan. Hasil pengukurannya adalah 100% sangat memuaskan dan 87,25% sangat bermanfaat. Hasil dari inisiatif pengabdian masyarakat ini menunjukkan bahwa lokakarya ini telah berdampak positif terhadap pemberdayaan masyarakat dan memperkuat kolaborasi interdisipliner.